The Effect of Integration Chemistry Learning Strategies to Growth Islamic Understanding in Quantum Chemistry - Lubis, Ervi Luthfi Sheila (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
This research have goals to know the effect of Integration-Based Chemistry Learning Strategies in Growth Islamic Understanding in Quantum Chemistry. Sample of this research are 9 Students of Grade 4 of Chemistry Study Program of the Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan Academic Year 2022/2023. This research use Quantitative research with 12 Essay Question Method as data collection. The result is students' Islamic understanding after studying Quantum Chemistry for one semester is decrease with percentage 85% and categorized as very good. Meaning that the chemistry learning strategy is based on integration in growth Islamic Understanding in quantum chemistry courses can improve students' understanding of Islam. With a chemistry learning strategy based on religious integration, it can create an understanding that chemistry, which has so far been considered abstract, can explain the greatness of Allah.